2016
DOI: 10.4238/gmr.15027707
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of PSA, ALP, ICTP, and BSP in prostate cancer patients and the significance of ROC curve in the diagnosis of prostate cancer bone metastases

Abstract: ABSTRACT. Bone metastasis is a common complication in prostate cancer patients that can cause bone pain and pathological fracture. This study tested serum levels of prostate specific antigen (PSA), alkaline phosphatase (ALP), bone sialoprotein (BSP), collagen type I pyridine crosslinking peptide (ICTP) in prostate cancer patients and the significance of the receiver operator characteristic (ROC) curve in the diagnosis of prostate cancer bone metastases. Eighty-three prostate cancer patients were enrolled inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 18 publications
1
23
0
1
Order By: Relevance
“…4,5 Classificatory systems based on clinical symptoms, diagnostic scales, radiological findings, assays of different substances and, primarily, choice of the optimal cutoff points to maximize the performance of diagnostic tests are the most common applications for ROC curves. [6][7][8][9][10][11] Figure 1A illustrates an example of a hypothetical test with high sensitivity and high specificity for diagnostic classification. This hypothetical test (test 1) has two distribution curves for the test results of sick and healthy individuals.…”
mentioning
confidence: 99%
“…4,5 Classificatory systems based on clinical symptoms, diagnostic scales, radiological findings, assays of different substances and, primarily, choice of the optimal cutoff points to maximize the performance of diagnostic tests are the most common applications for ROC curves. [6][7][8][9][10][11] Figure 1A illustrates an example of a hypothetical test with high sensitivity and high specificity for diagnostic classification. This hypothetical test (test 1) has two distribution curves for the test results of sick and healthy individuals.…”
mentioning
confidence: 99%
“…[28,29] A correlation has been investigated between bone metastasis and PSA level, ALP level and Gleason score, and consequently, correlations at varying levels have been mentioned in the literature. [30][31][32] Some authors recommended the use of bone scan in symptomatic patients or if alkaline phosphatase levels are > 90 U/l. [33] The authors described correlation between PSA value and both presence and number of metastases with a cutoff value of PSA of 10 ng/ml for negative bone scans.…”
Section: Discussionmentioning
confidence: 99%
“…Studies over recent years have suggested that, besides MMP family proteins, small integrin binding ligand N-linked glycoproteins (SIBLINGs) also regulate many of the activities required for the distant metastasis of tumor cells, especially for malignant bone metastases. Additionally, the serum levels of BSP and OPN (two primary proteins of the SIBLING family and the most frequently investigated) are often used to predict the occurrence of bone metastases ( 2 , 7 , 9 11 ). As mentioned previously, BSP and OPN contain an integrin-binding RGD (Arg-Gly-Asp) sequence that can bind to integrins to enhance the invasion and adhesion of tumor cells ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIBLINGs are overexpressed in many cancers ( 2 , 6 8 ). The level of SIBLING protein in serum is often used to predict the prognosis of many cancer patients, especially in patients with prostate and breast cancer ( 9 11 ). Two proteins in this family, namely, OPN (osteopontin) and BSP (bone sialoprotein), have garnered the most attention, and their reported levels of expression are closely correlated with tumor aggressiveness.…”
Section: Introductionmentioning
confidence: 99%